2014
DOI: 10.1155/2014/642385
|View full text |Cite
|
Sign up to set email alerts
|

Kojic Acid Production from Agro-Industrial By-Products Using Fungi

Abstract: A total of 278 different isolates of filamentous fungi were screened using synthetic medium for respective ability to produce kojic acid. Nineteen, six, and five isolates proved to be low, moderate, and high kojic acid producers, respectively. Levels of kojic acid produced were generally increased when shaking cultivation was used rather than those obtained using static cultivation. A trial for the utilization of 15 agro-industrial wastes or by-products for kojic acid production by the five selected higher koj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 36 publications
4
33
0
Order By: Relevance
“…Previous studies described that several species and strains of Aspergillus genus such as A. flavus, A. oryzae and A. parasiticus [57][58][59][60][61][62][63][64][65][66] are potent producers of kojic acid. Some earlier results showed that A. flavus strain 44-1 acquire 32.50 g/l of kojic acid by employing rotary shaker 66 .…”
Section: Recovery Of Kojic Acid and The Estimation Of Biomassmentioning
confidence: 99%
“…Previous studies described that several species and strains of Aspergillus genus such as A. flavus, A. oryzae and A. parasiticus [57][58][59][60][61][62][63][64][65][66] are potent producers of kojic acid. Some earlier results showed that A. flavus strain 44-1 acquire 32.50 g/l of kojic acid by employing rotary shaker 66 .…”
Section: Recovery Of Kojic Acid and The Estimation Of Biomassmentioning
confidence: 99%
“…Aspergillus Flavus was used for a higher yield of [32]. Yeast acted as a nitrogen source to enhance kojic acid production through metabolic activation.…”
Section: Photovoltaic Measurementmentioning
confidence: 99%
“…Various carbon sources (glucose, xylose, sucrose, starch, maltose, lactose or fructose) have been used as substrates for kojic acid production [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%